PENERAPAN MODEL PEMBELAJARAN CORE (CONNECTING, ORGANIZING, REFLECTING AND EXTENDING) UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN KESETIMBANGAN KELARUTAN (KSP) DI KELAS XI IPA SMAN 4 PEKANBARU - Nurhafni Nurhafni; John Azmi; Herdini Herdini (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Riau (UNRI), 2019)
The research about the CORE (Connecting, Organizing, Reflecting and Extending) model has been conducted in SMAN 4 Pekanbaru. The purpose of this research is to detemine wheterthe application of CORE learning can improve achievement and the influence of application of CORE learning model in class XI IPA SMAN 4 Pekanbaru on the subject solubility aquilibrium (Ksp). The type of this research is experimental research with experiment design randomized control group pretest-posttest. Sample of the research consisted of two classes, a class XI IPA 5 as an experimental class (implemented the CORE learning model) and class XI IPA 1 as the control class (without the CORE learning model). Test tecniques used as a tecnique in collecting research dats. T-test and coefficient determinasi was used as analysis technique. Based on the data analysis obtained t > t table is 5,71 > 1,66, meaning that the application of the CORE learning model can improve the student achievement on the subject solubility aquilibrium (Ksp) in class XI IPA SMA Negeri 4 Pekanbaru with the great influence of implementation of the CORE learning model on improving learning achievement is 31,178%.